2021
DOI: 10.31220/agrirxiv.2021.00037
|View full text |Cite
|
Sign up to set email alerts
|

In pursuit of a better broiler: carcass traits and muscle myopathies in conventional and slower-growing strains of broiler chickens.

Abstract: Selection for accelerated growth rate and high breast yield in broiler chickens have been associated with an increase in myopathies, including wooden breast (WB) and white striping (WS). To investigate effects of growth rate on carcass traits and incidence of myopathies, 14 strains were evaluated, encompassing 2 conventional (CONV; strains B and C: ADG0-48>60 g/d) and 12 slower-growing (SL) strains. The latter were categorized based on growth rate: FAST (strains F, G, I and M; ADG0-62=53-55 g/d), MOD (strai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 65 publications
(157 reference statements)
1
6
0
Order By: Relevance
“…(2021) . In addition, slower-growing broilers had lower prevalence of wooden breast compared to fast-growing broilers, which is supported by previous studies ( Dixon, 2020 ; Santos et al., 2021 ). Overall, slower-growing broilers showed lower performance, mortality and prevalence of wooden breast compared to fast-growing broilers.…”
Section: Discussionsupporting
confidence: 87%
“…(2021) . In addition, slower-growing broilers had lower prevalence of wooden breast compared to fast-growing broilers, which is supported by previous studies ( Dixon, 2020 ; Santos et al., 2021 ). Overall, slower-growing broilers showed lower performance, mortality and prevalence of wooden breast compared to fast-growing broilers.…”
Section: Discussionsupporting
confidence: 87%
“…Although the presence of WB and WS have been reported in some slow and fast growing Canadian broilers ( Santos et al, 2021 ), no systematic studies have addressed the morphological characteristics and severity of breast myopathies (SM, WB, and WS) in commercial Canadian broilers. Therefore, the objectives of the study were to describe the physical and histological characteristics of SM, WB, and WS from commercial broiler chicken flocks in Ontario, Canada, and to assess associations between the severity of myopathies and physical and histological characteristics of the affected breast muscle fillets.…”
Section: Introductionmentioning
confidence: 99%
“…These categories were also the lightest birds at TW 1, suggesting that differences in BW contributed more to performance in the LTL than did genetic potential for growth rate. The lower BW of ONV birds despite their greater growth performance was mainly due to the processing age that occurred earlier than the expected time for CONV strains to reach 2.1 kg ( Santos et al, 2021a ). On the other hand, the lower BW of SLOW birds is attributed to their reduced growth rate (ADG <50 g/d) compared to the other categories ( Torrey et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…The results obtained in the group obstacle test partially complement the observations obtained in the LTL test, supporting the hypothesis that selection for accelerated and early muscle accretion may have negative effects on mobility in broiler chickens. The lower number of crossings observed in FG birds may be due to their body conformation (including large breast muscles: Santos et al, 2021a ; and short legs: Santos et al, 2021b ) requiring an altered gait to increase their stability while walking ( Paxton et al, 2014 ) Corr et al (2003b) . suggested that the gait of FG birds is inefficient, rapidly tiring the birds and leading to low activity levels.…”
Section: Discussionmentioning
confidence: 99%